Effect of taxanes on the cell proliferation of thyroid papillary carcinoma - Gerashchenko, O. L.; Zhuravel, E. V.; Pushkarev, V. V.; Pogrebnoy, P. V.; Tronko, M. D. (Reports of the National Academy of Sciences of Ukraine, 2014)
We studied the effect of taxanes in ultralow concentrations on the proliferative activity of papillary thyroid cancer cells, as well as on the activity and the expression of several cell cycle regulatory factors. It is shown that docetaxel inhibited the proliferation of TPC1 cell line. The reason for cell cycle inhibition may be a tumor suppressor pRb dephosphorylation and increasing the expression of an inhibitor of cyclin-dependent kinases p21Waf1/Cip1.